Pengaruh Kurikulum Merdeka Dalam Penggunaan Canva Sebagai Media Pembelajaran di MAN 1 Kulon Progo - Rosyada Ayu Fatimah; Olvy Mailandari; Jany Fitria Khoirunnisa; Wahyu Lestari; Fuad Dirahman (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Canva is a medium that can help teachers convey material so that it is easily understood by students. Canva is an application that can be developed in the process of creating learning media. The aim of this research is to improve the quality of teachers by developing learning media that is in accordance with the independent learning curriculum program. In this independent learning curriculum teachers are required to be able to adapt to technology, however there are still many teachers who have not mastered various technological features. One of them is the Canva application because not all of its features are free, offline access is not available, the hyper-contect learning module can only be done with two applications and of course the Canva application's internet signal can be affected. The results of this research are that educators or teachers are expected to be able to develop more interesting learning media, because this really helps clarify the material that will be conveyed to students in implementing the independent learning curriculum. It is hoped that this research can make a contribution to education activists, especially teachers and students, by utilizing Canva as a media solution to facilitate the implementation of the independent curriculum.